Influência do tráfego intracelular do Trypanosoma cruzi e resposta celular à infecção no desenvolvimento intracelular do parasito - Patrícia Pereira Dias (2017)
Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, presents a variable clinical course, varying from asymptomatic to serious debilitating pathologies with cardiac, digestive or cardio-digestive impairment. Previous studies using two clonal T. cruzi populations, Col1.7G2 (T. cruzi I) and JG (T. cruzi II) demonstrated that there was a differential tissue distribution of these parasites during infection in BALB/c mice, with predominance of JG in the heart. Increased JG adaptation by cardiac muscle was later confirmed by in vitro infection studies in primary cardiomyocyte cultures. Thus, selection may primarily be a result of the direct interaction between parasite and host cell. Additionally, it was observed that the selection is dependent not only on parasite invasion, but mainly on the intracellular multiplication rate of the parasite. Little is known about the mechanisms that determine this tissue selection. The host cell when infected responds to this infection producing several factors such as, reactive oxygen species, cytokines, among others. In agreement with previous data from the literature we show here that JG strain presents a higher intracellular multiplication rate when compared to Col1.7G2 clone. We also showed that cardiomyocytes in culture respond to infection with production of reactive oxygen species (ROS) and that the levels of ROS are higher in cultures infected with JG, while JG presents less anti-oxidant enzymes. Additionally, inhibition of oxidative stress interferes with intracellular multiplication rate of JG, but not Col1.7G2. ROS, was able to induce higher levels of signaling molecules in JG, such as calcium and anion superoxide, which may be contributing to the faster intracellular multiplication of this clonal population of the parasite. Data presented here suggest that certain levels of ROS might be important for signaling and induction of parasite intracellular multiplication.